An Investigation on Forage Yield Capacity of Kermes Oak (Quercus coccifera L.) and Grazing Planning of Mediterranean Maquis Scrublands for Traditional Goat Farming - Ahmet Tolunay; Elif Adıyaman; Ayhan Akyol; Duygu İnce; Türkay Türkoğlu; Veysel Ayhan (The Scientific World Journal)
This study investigated grazing capacities of maquis scrubland and preparation principles of grazing management in forest resources. Kermes oak (Quercus coccifera L.), which is widespread as a main shrub species in maquis vegetation in Turkey, and pure hair goats (Capra hircus L.) feeding on shoots and leaves of this shrub were selected for study. The study was conducted in two stages. Green leaf and shoot samples were taken from kermes oaks in the first stage and the amount of green herbage yield (g*m−1) and dry matter yield (kg*ha−1) that may be obtained per unit area from these samples was identified. The considered amount of dry matter consumed by pure hair goats daily and the number of goats being fed within 1 year on land of 1 ha according to different land coverage rates of kermes oaks (goat head*ha*yr) were calculated. In the second stage, grazing capacities of sample areas where kermes oak spread were identified and compared with the grazing plan prepared by the forestry administration for this area. Forage yield variance according to land coverage rates of maquis scrublands should be considered when determining optimum animal numbers for grazing per area for sustainable goat farming.